Effect of exercise on ovulation: A systematic review - Hakimi, O.; Cameron, L.-C. (Sports Medicine, 2017)
Background: Infertility has been described as a devastating life crisis for couples, and has a particularly severe effect on women, in terms of anxiety and depression. Anovulation accounts for around 30% of female infertility, and while lifestyle factors such as physical activity are known to be important, the relationship between exercise and ovulation is multi-factorial and complex, and to date there are no clear recommendations concerning exercise regimes. Objectives: The objective of this review was to systematically assess the effect of physical activity on ovulation and to discuss the possible mechanisms by which exercise acts to modulate ovulation in reproductive-age women. This was done with a view to improve existing guidelines for women wishing to conceive, as well as women suffering from anovulatory infertility. Search Methods: The published literature was searched up to April 2016 using the search terms ovulation, anovulatory, fertility, sport, physical activity and exercise. Both observational and interventional studies were considered, as well as studies that combined exercise with diet. Case studies and articles that did not report anovulation/ovulation or ovarian morphology as outcomes were excluded. Studies involving administered drugs in addition to exercise were excluded. Results: In total, ten interventions and four observational cohort studies were deemed relevant. Cohort studies showed that there is an increased risk of anovulation in extremely heavy exercisers (>60 min/day), but vigorous exercise of 30-60 min/day was associated with reduced risk of anovulatory infertility. Ten interventions were identified, and of these three have studied the effect of vigorous exercise on ovulation in healthy, ovulating women, but only one showed a significant disruption of ovulation as a result. Seven studies have investigated the effect of exercise on overweight/obese women suffering from polycystic ovary syndrome (PCOS) or anovulatory infertility, showing that exercise, with or without diet, can lead to resumption of ovulation. The mechanism by which exercise affects ovulation is most probably via modulation of the hypothalamic-pituitary-gonadal (HPG) axis due to increased activity of the hypothalamic-pituitary-adrenal (HPA) axis. In heavy exercisers and/or underweight women, an energy drain, low leptin and fluctuating opioids caused by excess exercise have been implicated in HPA dysfunction. In overweight and obese women (with or without PCOS), exercise contributed to lower insulin and free androgen levels, leading to the restoration of HPA regulation of ovulation. Conclusions: Several clear gaps have been identified in the existing literature. Short-term studies of over-training have not always produced the disturbance to ovulation identified in the observational studies, bringing up the question of the roles of longer term training and chronic energy deficit. We believe this merits further investigation in specific cohorts, such as professional athletes. Another gap is the complete absence of exercise-based interventions in anovulatory women with a normal body mass index (BMI). The possibly unjustified focus on weight loss rather than the exercise programme means there is also a lack of studies comparing types of physical activity, intensity and settings. We believe that these gaps are delaying an efficient and effective use of exercise as a therapeutic modality to treat anovulatory infertility.